Mycobacterium tuberculosis in central Ethiopia: drug sensitivity patterns and association with genotype. (May 2017) - Bedewi, Z.; Mekonnen, Y.; Worku, A.; Medhin, G.; Zewde, A.; Yimer, G.; Pieper, R.; Ameni, G.
Abstract: Drug resistance tuberculosis (TB) and the emergence of multidrug resistant (MDR) isolates are significant concerns regarding TB control programs in several countries. This study was undertaken to evaluate the drug sensitivity of Mycobacterium tuberculosis and to assess its association with strains and lineages of M. tuberculosis. A total of 279 M. tuberculosis strains isolated from Central Ethiopia were tested for their drug sensitivity patterns to first line TB drugs using the conventional proportion method on Löwenstein Jensen media. The association between drug sensitivity and strain type was assessed on 263 isolates of the 279 isolates. Of the 268 M. tuberculosis isolates obtained from new cases, 209 (78%) were susceptible to first line TB drugs, and 59 (22.2%) bacterial isolates were resistant to at least one of the first line drugs. The highest mono-resistance (7.5%) pertained to streptomycin (STM). Remarkably, seven of eleven isolates (63.6%) previous treatment for TB were resistant to at least one of the first line drugs. The prevalence of MDR-TB was 1.5% (4/268) for newly identified TB cases, all of which were members of the Euro-American Lineage. There was no statistically significant association (P > 0.05) between drug sensitivity, and either strains, sub-lineages or main lineages of M. tuberculosis . A significant proportion of M. tuberculosis was resistant to at least one first line anti-TB drug. Moreover, the frequencies of resistance to either isoniazid or rifampicin were high compared to data that were previously reported in some part of the country.